Fostering Historical Thinking Skills with Ethnophotography-based Teaching Materials in Elementary Schools - Iin Purnamasari (Paramita: Historical Studies Journal, 2023)
This study aims to determine the practicality and effectiveness of ethnophotography-based teaching materials in social studies learning in elementary schools. This research is research and development by adopting the ADDIE model (analysis, design, development, implementation, and evaluation). The data collection instruments in this study were the feasibility of lecturers, practicality sheets for subject teachers and peers, student readability sheets, and pretest and posttest questions for student learning outcomes. The data collection instrument is based on the learning of the supervisor, assessment by experts, subject teachers, peers, and student trials. The implementation phase of the use of teaching materials developed for fourth-grade students at SDN Karangasem 13. The trials carried out at this stage were product feasibility tests, readability, and pretest posttests for fourth-grade students. The results showed increased learning outcomes after students used ethnophotography-based teaching materials. Evidenced by the n-gain value of 0.49 in the medium category. The evaluation stage includes an evaluation carried out at each stage of the ADDIE model. The data analysis technique used is the manova test and n-gain. The results showed that the developed ethnophotography teaching materials were suitable for social studies learning. The ethnophotography teaching materials are practical and effective in improving the learning outcomes of elementary school students. This teaching material is also essential to foster awareness of historical thinking.Penelitian ini bertujuan untuk mengetahui kelayakan, kepraktisan, dan keefektifan bahan ajar berbasis etnofotografi dalam pembelajaran IPS di Sekolah Dasar. Penelitian ini adalah research and development dengan mengadopsi model ADDIE (analyze, design, development, implementation, dan evaluation). Instrumen pengumpulan data dalam penelitian ini berupa kelayakan dosen ahli, lembar kepraktisan guru mata pelajaran dan teman sejawat, lembar keterbacaan siswa, soal pretest dan posttest hasil belajar siswa. Instrumen pengumpulan data dikembangkan berdasarkan peninjauan dosen pembimbing, penilaian oleh ahli, guru mata pelajaran, teman sejawat dan ujicoba siswa. Tahap implementation meliputi penggunaan bahan ajar yang telah dikembangkan pada siswa kelas IV SDN Karangasem 13. Ujicoba yang dilakukan pada tahap ini adalah uji kelayakan produk, uji keterbacaan, dan pretest posttest pada siswa kelas IV, dengan hasil menunjukkan adanya peningkatan hasil belajar setelah siswa menggunakan bahan ajar berbasis etnofotografi dibuktikan dengan nilai n-gain 0,49 dengan kategori sedang. Tahap evaluation meliputi bentuk evaluasi yang dilakukan pada setiap tahapan model ADDIE. Teknik analisis data yang digunakan dengan uji manova dan n-gain. Hasil penelitian menunjukkan bahwa bahan ajar etnofotografi yang dikembangkan layak untuk digunakan dalam pembelajaran IPS. Bahan ajar etnofotografi tersebut praktis digunakan, dan efektif untuk meningkatkan kemampuan hasil belajar siswa sekolah dasar. Bahan ajar ini juga sangat diperlukan untuk menumbuhkan kesadaran berpikir historis.